Definitions, methodological and statistical issues for phase 3 clinical trials in chronic myeloid leukemia: a proposal by the European LeukemiaNet - Guilhot, Joëlle; Saußele, Susanne; Hehlmann, Rüdiger (Blood, 2012)
The treatment policy of chronic myeloid leukemia (CML), particularly with tyrosine kinase inhibitors, has been influenced by several recent studies that were well designed and rapidly performed, but their interpretation is of some concern because different end points and methodologies were used. To understand and compare the results of the previous and future studies and to translate their conclusion into clinical practice, there is a need for common definitions and methods for analyses of CML studies. A panel of experts was appointed by the European LeukemiaNet with the aim of developing a set of definitions and recommendations to be used in design, analyses, and reporting of phase 3 clinical trials in this disease. This paper summarizes the consensus of the panel on events and major end points of interest in CML. It also focuses on specific issues concerning the intention-to-treat principle and longitudinal data analyses in the context of long-term follow-up. The panel proposes that future clinical trials follow these recommendations.